Treatment of hospital wastewater by anodic oxidation using a new approach made by combining rotation with pulsed electric current on Cu-SnO2–Sb2O5 rotating cylinder anode - Falah H. Abd; Ali H. Abbar (Heliyon)
A high-efficiency, low-cost Cu-SnO2-Sb2O5 anode was prepared using a novel approach that combines the effects of rotation with pulsed current. The effects of operating variables such as rotation speed (50–250 rpm), pulsed current density (5–20 mA/cm2), and electrodepostion time (30–60 min) on the morphology and activity of Cu-SnO2–Sb2O5 anode were investigated. The structure of Cu-SnO2–Sb2O5 anode was examined by SEM, EDS, and XRD techniques. The results showed that using higher rotation speed combined with pulsed current gave better properties of Cu-SnO2–Sb2O5 anode in terms of higher oxidation activity and longer service life time. The optimum conditions for preparing Cu-SnO2–Sb2O5 anode were a pulsed current density of 10 mA/cm2, rotation speed of 250 rpm, and deposition time of 60 min. The prepared anode has the ability to remove methylene blue (MB) with an efficiency of 99.7 %. It has an excellent service life of 30 h. Additionally, the prepared anode has the potential to remove COD from hospital wastewater with 85 % efficiency by applying a current density of 10 mA/cm2 for 120 min at an initial pH of 3 where an energy consumption of 2.85 kWh/kg was claimed. The novel approach of combining rotation with pulsed electric current in preparing Cu-SnO2-Sb2O5 anode offers enhanced methylene blue degradation efficiency and extended anode life, demonstrating potential for industrial-scale hospital wastewater treatment.